THE COMPARATION BETWEEN GERMANY EDUCATION AND INDONESIA EDUCATION - Mardianah (Corolla International Conference, 2022)
The educational system in Germany is well-organized. It began with teacher hiring, curriculum development, and funding, among other things. These advantages should serve as a model for developing education systems in other countries. Other countries can learn from Germany’s experience in improving educational quality. The German or East German democratic republic’s general education system reflects diverse components of German educational tradition, as well as adaptations of Soviet models. After four years of elementary school, the one-ladder education system, founded in 1945 at the outset of the Soviet postwar occupation, ended the separation of children into separate schools. The objective of this research was to know the comparison between Gemarny education system and Indonesia education system. This research started from the basif aspect of each school such as the history of education, objective of education, basic philosophy, Germany education system, level of education, and education comparison between Germany and Indonesia. Then, Funding, methodological flaws in the national education system, teaching attitude values rather than report values, and education administration are all factors to consider when comparing education in Germany and Indonesia.